Dolphin Morbillivirus Epizootic Resurgence, Mediterranean Sea - Raga, Juan-Antonio (Centers for Disease Control and Prevention, 2008)
In July 2007, >100 striped dolphins, Stenella coeruleoalba, were found dead along the coast of the Spanish Mediterranean. Of 10 dolphins tested, 7 were positive for a virus strain closely related to the dolphin morbillivirus that was isolated during a previous epizootic in 1990.